Enjeux des Activités Humaines dans le Maintien de la Diversité Végétale des Forêts Marécageuses de la Sous-Préfecture de Grand-Lahou sur le Littoral Ivoirien - Alexandre, Yao Koffi; Marcel, Yoro Blé; Yves, Adou Yao Constant; Célestin, Amani Yao (European Scientific Journal, ESJ, 2019)
Human activities are recognized as potential threats to the survival of swamp forests and their resources in the rural environment of the GrandLahou Sub-Prefecture. This study proposes to question the relations between the riverside communities and these environments, in a perspective of valorization, use and sustainable management of these environments, as well as their resources. As part of a socioecological approach and based on a qualitative analysis, the information was collected through documentary research, direct observation and semi-structured group and individual interviews with administrative, customary and rural households. Near the swamp forests of the sub-prefecture of Grand-Lahou for a staff of one hundred and forty-three people (146). With systemic and phenomenological analysis tools, the processing and interpretation of the collected data were subjected to statistical data analysis and qualitative content analysis. Thus, the study made it possible to understand that the swamp forests of the subprefecture of Grand-Lahou are an element of the landscape characteristic of the natural, socio-economic and cultural inheritance of this sub-prefecture. They participate through their natural resources in the livelihoods of neighboring communities. For example, according to the data collected, 58.3% of the respondents use them as agricultural areas(perennial crops, food crops (rice, corn,) and vegetables). And for more than 80% of them, they constitute reserves of organic raw materials (lumber and construction, hunting, fishing, pharmacopoeia, fuel, etc.). However, among the accepted human activities of these environments, some, such assustainable agriculture, capitalist logging, hunting, gold panning and agricultural pollution with pesticides, constitute threats that lead to the disappearance or the degradation of these environments at the local level. Les activités humaines sont admises comme des menaces potentielles pour la survie des forêts marecageuses et de leurs resources dans le milieur rural de la Sous-préfecture de Grand-Lahou. Cette étude se propose d’interroger les relations entre les communautés riveraines et ces milieux, dans une perspective de valorisation, d’utilisation et de gestion durable desdits milieux, ainsi que de leurs ressources. S’inscrivant dans une approche socioécologique et partant d’une analyse qualitative, les informations ont été collectées à travers la recherche documentaire, l’observation directe et des entretiens semi-directifs de groupe et individuels auprès des autorités administratives, coutumières et ménages ruraux vivant à proximité des forêts marécageuses de la sous-préfecture de Grand-Lahou pour un effectif de cent quarante-trois personnes (146). Avec les outils d’analyse systémique et phénoménologique, le traitement et l’interprétation des données recueillies ont été soumis à l’analyse statistique des données et à l’analyse de contenu qualitative. Ainsi, l’étude a permis de comprendre que les forêts marécageuses de la sous-préfecture de Grand-Lahou sont un élément du paysage caractéristique du patrimoine naturel, socioéconomique et culturel de ladite sous-préfecture. Elles participent grâce à leursressources naturelles aux moyens d’existence des communautés riveraines en matière d’alimentation, d’habitation, d’artisanat, pharmacopée, etc. Cependant, au nombre des activités humaines admises de ces milieux, certaines, telles que l’agriculture pérenne, l’exploitation forestière de type capitaliste, la chasse, l’orpaillage et les pollutions agricoles aux pesticides, constituent des menaces qui conduisent à la disparition ou à la dégradation de ces milieux à l’échelle locale.